A influência dos capitais na trajetória dos empreendedores de startups de tecnologia no Brasil - Freire, Clarissa Dourado (Universidade Federal de São Carlos, 2021)
Several studies highlight the positive contribution of entrepreneurship to economic and social development, given the relevance of the subject it is possible to observe the growth of studies about entrepreneurship, especially from the 1990s with the advent of technology startups. One of the main questions is to understand how an individual becomes an entrepreneur, despite the diversity of studies in different fields of knowledge, there is a predominance of mainstream economics, in which there is an idealization of the entrepreneur as an actor endowed with unique characteristics, who acts autonomously, disregarding the social context. This paper seeks to offer an alternative to this paradigm and propose an expansion in the analysis of the variables that make an individual an entrepreneur, using Pierre Bourdieu's perspective of capitals as a theoretical lens. The objective of this work is to analyze how entrepreneurs mobilize and convert capitals along their trajectories and what is the importance of these capitals for the foundation and development of technology startups. To this end we divided the work into three stages, the first stage consists of a Systematic Literature Review (RSL), with the objective of understanding how the capitals perspective has been employed in the study of entrepreneurship and to know the entrepreneur, identify the categories of capitals and identify possible research gaps. After the RSL, with the identification of the categories of capitals, we have the second stage, of qualitative nature, built through five case studies with entrepreneurs of technology startups, in which we seek to analyze how the capitals are mobilized and converted along the trajectory of entrepreneurs, giving rise to the circularity of capitals, as well as to analyze the importance of these capitals for the foundation and development of startups. The third and last stage, of a quantitative nature, was built from a survey with 192 questionnaires applied to entrepreneurs of technology startups and the use of Multiple Correspondence Analysis, in which we sought to perform a descriptive analysis of the entrepreneurs, to identify the capitals mobilized and converted throughout their trajectories, as well as to understand if the social space of the entrepreneurs facilitates the access to capitals and resources employed in the foundation and development of the startups, legitimating the position of the entrepreneurs in the social space. The results indicate that there is a search for alternatives to the dominant perspectives for the study of entrepreneurship and the entrepreneur, and Bourdieu's perspective emerges as a possibility, being employed in this work. Entrepreneurs mobilize economic, cultural, social, and symbolic capital, which are converted and reconverted in a dynamic process we call the circularity of capitals. This set of capitals and this process gives rise to the entrepreneurial capital, which results from the use of these capitals in the foundation and development of startups. Therefore, access to these capitals is fundamental to the entrepreneurial action of startup founders, but they are not homogeneously distributed in the social space. Our research highlights on this discussion and proposes to be an instrument for public policies that facilitate access and dissemination of these capitals.
The influence of capital on the trajectory of technology startups entrepreneurs in Brazil
Keywords: Empreendedor; Startup; Tecnologia; Bourdieu; Capitais; Trajetórias; Entrepreneur; Technology; Capitals; Trajectory; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO DE EMPRESAS; ENGENHARIAS::ENGENHARIA DE PRODUCAO